2015
DOI: 10.1152/jn.00777.2014
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing intrinsic from extrinsic factors underlying firing rate saturation in human motor units

Abstract: During voluntary contraction, firing rates of individual motor units (MUs) increase modestly over a narrow force range beyond which little additional increase in firing rate is seen. Such saturation of MU discharge may be a consequence of extrinsic factors that limit net synaptic excitation acting on motor neurons (MNs) or may be due to intrinsic properties of the MNs. Two sets of experiments involving recording of human biceps brachii MUs were carried out to evaluate saturation. In the first set, the extent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 90 publications
6
65
1
Order By: Relevance
“…This finding is nearly identical to that reported previously for a population of 136 human biceps brachii MUs (Fuglevand et al . ). In contrast, during the ascending phase of contractions involving sural nerve stimulation, the proportion of MUs with firing rate profiles best fitted by exponential functions (11/23) was similar to that designated as linear (9/23) and not significantly different from that expected by chance (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…This finding is nearly identical to that reported previously for a population of 136 human biceps brachii MUs (Fuglevand et al . ). In contrast, during the ascending phase of contractions involving sural nerve stimulation, the proportion of MUs with firing rate profiles best fitted by exponential functions (11/23) was similar to that designated as linear (9/23) and not significantly different from that expected by chance (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Previously, we have shown that force and firing rate data for individual MUs during graded increases in isometric force are typically best fitted as a saturating function in the form of a rising exponential (Fuglevand et al . ). As such, we first fitted each phase of force–firing rate data for each trial with an equation of that form: R(F)=Rtrueprefixmax(1e(FF th )/φ)+Rtrueprefixminwhere R ( F ) represents the rate ( R ) of spiking as a function of muscle force ( F ), R max is the maximum rate of spiking, e is the base of the natural logarithms, F is normalized isometric force, F th is the threshold force at which a unit begins to discharge, and R min is the minimum rate of spiking at recruitment threshold.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Increasing the firing rate above this rate is not compatible with optimal contraction control (Bigland-Ritchie and Woods, 1984). Therefore, the rate saturation observed by many researchers in low-threshold human MUs is not surprising (Bigland and Lippold, 1954; Gydikov and Kosarov, 1974; Monster and Chan, 1977; Bellemare et al, 1983; Moritz et al, 2005; Bailey et al, 2007; Fuglevand et al, 2015). …”
mentioning
confidence: 89%
“…Therefore, the working mean firing rate range varies a remarkable 8-10 fold, although muscle seems most responsive to rates between 10 and 40 Hz (30), and these are the more frequently recorded rates from large numbers of MUs.…”
Section: Changes In the Neuromuscular Pathway With Fatiguing Exercisementioning
confidence: 99%